(untitled) (International Journal of Engineering and Computer Science, 2016)
At present juncture we are facing a drastic depletion of our available energy resources in the form of fuels for automobiles, as a major source for the functioning of power plants and industries, in combustion, etc. If the consumption of the non-renewable energy resources continued in the same manner then the day is not far enough when there will be disastrous consequences existing on this planet. In order to cope up with this serious issue, use of renewable energy resources must be practiced and implemented on a large scale. There are several sources of renewable energy available nowadays. One of the solutions for these problems is gasification- a process in which there is production of energy from biomass, solid waste, etc. which is easily available in our surroundings and is produced on a high rate on daily basis. This will be contributing towards the growth of renewable sources of energy. In this article an attempt has been made to study about the gasifying process, gasifiers, types of gasifiers, need of gasifiers, importance of gasifiers, reactions involved in the process, advantages of gasifiers.